EVALUATING THE ECONOMIC AND SOCIAL IMPLICATIONS OF FREE PUBLIC HIGHER EDUCATION - Sevinchoy Shermatova (TILSHUNOSLIK VA CHET TILLARNI O‘QITISHDA ZAMONAVIY RAQAMLI TEXNOLOGIYALARDAN FOYDALANISH MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Have you ever questioned why, in a world where education is viewed as a fundamental right, countless students still face challenges in paying for university? The cost of higher education has risen significantly, posing challenges for numerous young individuals. This article examines the concept of free public universities by studying its economic and societal impacts. Rather than concentrating solely on personal accountability, this study explores how systems like government funding, economic disparity, and public policy influence educational access. It also examines if free education is a feasible solution or a financial strain for nations.